Value Relevance of IFRS Adoption in ASEAN-5 Countries: Does Presentation Matters? - Aria Farah Mita; Sylvia Veronica Siregar; Viska Anggraita; Fitriany Amarullah (Journal of Accounting and Investment, 2020)
Research aims: This study discusses a recent development in the adoption of International Financial Reporting Standard (IFRS) in ASEAN. The objective of this study is to examine the value relevance of the Other Comprehensive Income (OCI) after the revision of the International Accounting Standard (IAS 1) about the presentation of financial statements. Primarily, this study will examine whether the relocation of the OCI from the Statement of Changes in Owners' Equity to the Statement of Comprehensive Income will increase the value relevance.Design/Methodology/Approach: This study compares the value relevance of other comprehensive income (OCI) one year before and after the adoption of IAS 1 in each country. The study focuses on ASEAN 5 countries, namely Indonesia, Malaysia, Philippine, Singapore, and Thailand.Research findings:  The result of the study found that the OCI has higher value relevance after the adoption of IAS 1.Theoretical contribution/ Originality:.This study extends previous studies around IFRS adoption, which mostly focused on European countries. The study about IFRS adoption in ASEAN countries is limited. This study presents a unique setting since most of the Countries in ASEAN adopted IAS 1 not in the same year as the year enacted by the IASB. This study will contribute to the recent development in accounting standard, which shows the adoption of IAS No. 1 as part of the IFRS adoption in ASEAN will increase the value relevance of the financial statement.Practitioner/Policy implication: This study will imply for the Practitioner and Policymakers that the benefits of IFRS adoption aimed to improve the quality of financial reports, so users can more easily and readily process that information about company performance.Research limitation/Implication: This study only focuses on total OCI. This study does not analyze the impact of the adoption of revised IAS 1 for each items of OCI, such as available for sale component, revaluation surplus or translation component. The result is consistent with the proponent of the IFRS adoption that the revision of IAS 1 will increase the usefulness of the financial statement.